Three new species of the genus Amynthas (Oligochaeta: Megascolecidae) from Guangxi Zhuang Autonomous Region, China - Li, Jiali; Jiang, Jibao; Jin, Qing; Yuan, Zhu; Liu, Hong; Qiu, Jiangping (Zootaxa, 2024)
Three new earthworm species of the genus Amynthas Kinberg, 1867 were found in Guangxi Zhuang Autonomous Region, China: Amynthas huapingensis sp. nov., Amynthas retentus sp. nov. and Amynthas linguiensis sp. nov. Amynthas huapingensis sp. nov. belongs to Amynthas corticis-group characterized by having four pairs of spermathecal pores in 5/6–8/9; Amynthas retentus sp. nov., without spermathecal pores, belongs to Amynthas illotus-group; Amynthas huapingensis sp. nov. and Amynthas retentus sp. nov. have similar characteristics of male porophores medially surrounded by 2–3 genital papillae in a pulvinate pad within the male pore area. Amynthas linguiensis sp. nov. has variable spermathecal pores, three pairs in 6/7–8/9 or four pairs in 5/6–8/9. And its male pores each on the center of a large elliptical glandular porophore which extends from 1/4xvii to 1/4xix. The morphological comparison and COI gene data of these three new species and their similar species are given in this paper.